High and steep slope soil-fixing and conserving type reconstructed soil and preparation method thereof
Patent Information
- Application Number
- CN202611170704.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-04
AI Technical Summary
[0006]针对现有高陡边坡覆土材料存在以下尚未解决的技术问题:1)采用水泥、石灰或碱激发工业固废作为胶凝材料,体系碱度过高(pH>11),抑制植物种子萌发和根系穿行,且水化产物脆性大、易开裂;2)常规有机纤维与无机基体之间仅为物理摩擦,缺乏化学键合,增强效果随服役时间急剧衰减;3)肥料多为速效化肥直接掺混,覆土后3~6个月养分随雨水大量淋失,导致植被中后期缺肥衰败;4)对废弃混凝土等城市固废的资源化利用率较低,且制备过程常需高温热熔(>160℃)或蒸汽养护,能耗高
[0029] 1. Excellent erosion resistance: The dry density of the reconstructed soil of this invention is 0.70~0.95g/cm³, the saturated compressive strength is ≥1.2MPa, and the erosion loss rate is ≤6.5% after 2 hours under the conditions of 55° slope and 120mm/h rainfall. This effect is due to the high elastic recovery ability of the material given by the organic-inorganic interpenetrating network formed by lithium magnesium silicate and hydrogel, the density reduction by ammonium bicarbonate foaming, and the in-situ cementing effect of hydroxyapatite.
Smart Images

Figure CN122667905B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of soil covering reconstruction and ecological restoration technology for steep slopes, specifically involving a soil stabilization and conservation type of reconstructed soil for steep slopes and its preparation method. Background Technology
[0002] Mining activities in my country's metal and non-metal mines have generated a large number of steep rock slopes and spoil heap slopes with an angle of more than 45°. These slopes generally lack a soil matrix layer and are prone to soil erosion under rainfall. Natural vegetation recovery is extremely difficult. The core task of their ecological restoration is to construct a soil-like matrix layer with sufficient mechanical stability and water erosion resistance on the interface of hard or loose rock fragments.
[0003] Currently, the materials used for backfilling and restoration of mine slopes mainly include topsoil spraying substrates, vegetation concrete, fiber soil, and solid waste-based artificial soil. However, existing technologies have the following technical problems: traditional topsoil relies heavily on natural cultivated soil or peat, damaging arable land and wetland resources; cement-based or alkali-activated solid waste cementitious material systems have excessively high alkalinity (pH>11), severely inhibiting seed germination and root penetration; conventional organic fibers only have physical friction with the inorganic matrix, and are easily pulled out under alternating wet and dry conditions and freeze-thaw cycles, resulting in a rapid decline in the reinforcing effect; existing fertilizers are mostly fast-acting chemical fertilizers directly mixed in, and nutrients are largely leached away by rainwater 3-6 months after backfilling, leading to nutrient deficiency and vegetation decline in the later stages; existing technologies have low resource utilization rates for urban solid waste such as waste concrete, and the preparation process often requires high-temperature hot melting (>160℃) or steam curing, resulting in high energy consumption.
[0004] The closest prior art to this application includes: Chinese invention patent CN113598013B (authorization announcement date June 17, 2022) discloses a rock aging and repair agent for fresh rock wounds on steep slopes, composed of waste fruit fermentation products, organic planting soil, plant gum, natural mineral powder, organic acid, and water-retaining agent. This repair agent can form a water-retaining and breathable thin layer after being sprayed onto the rock wound, but its cementing effect mainly relies on the physical adhesion of the plant gum, lacking chemical mineralization cementation. It has insufficient erosion resistance under heavy rainfall conditions and does not involve long-term slow release of nutrients. Chinese invention patent CN116621548B (authorization announcement date October 10, 2023) discloses a low-carbon recycled ecological concrete with high vegetation performance, using red brick fragments as recycled aggregate, low-alkalinity sulfoaluminate cement (16~21 wt%) as cementing material, and combining it with gap-filling soil and topsoil to form a three-layer structure. Although this technology reduces the alkalinity of the system, it still relies on cement hydration and bonding, and the hydration products are brittle and prone to cracking. Although the topsoil contains water-retaining resin and phosphogypsum, the nutrients are still mainly physically mixed and lack a chemical slow-release mechanism. Moreover, the preparation process requires 28 days of curing of precast slabs, resulting in a long construction cycle. Chinese invention patent CN119801019B (authorization announcement date: January 30, 2026, patentee: Fuzhou University) discloses an ecological restoration structure and method for steep rock slopes based on bio-solidification technology. The bio-solidified coarse soil layer is fixed to the slope surface by anchor bolts, metal mesh, and square solidification cavities. The coarse soil containing bio-mud is solidified by spraying soybean enzyme treatment liquid to form a bio-solidified coarse soil layer, and then a vegetation base layer is sprayed on its surface.This technology utilizes soybean enzymes to induce calcium carbonate precipitation for bio-solidification, but its construction requires the laying of numerous engineering components such as metal mesh, anchor bolts, and solidification cavities, making the process complex and costly. Furthermore, the bio-solidified coarse-grained soil layer is only 30-50mm thick, with limited erosion resistance, failing to address the problem of easy loss of topsoil material on steep slopes under heavy rainfall conditions. Chinese invention patent CN114600731B (authorization announcement date November 25, 2022, patentee: Chengdu University of Technology) discloses a lightweight material for vegetation restoration on steep slopes, prepared from planting soil, peat moss, plant fibers, chemical fibers, water-retaining agents, and slow-release fertilizers. This material has a density of 0.3-0.5 g / cm³, a porosity of 52-58%, and a water retention rate ≥90%. However, this technology still faces significant challenges. Relying on natural peat soil (40-60 parts by weight) and planting soil, it damages peat wetland resources. Its preparation process requires hot melting at a high temperature of 160-220℃ for 5-8 hours, which consumes a lot of energy. After the material is formed, it is modified by spraying with biological bacterial liquid, but it lacks chemical mineralization and bonding. The aggregate particles are only physically bonded, and it is prone to structural loosening and strength reduction during long-term service. Chinese invention patent CN120858835B (authorization announcement date December 16, 2025, patentee: Second Geological Team of Sichuan Province) discloses an improved soil ecological substrate for ecological slope protection and its preparation method and application, including an anti-sliding, UV-resistant and freeze-thaw resistant layer and a soil adaptation layer. The anti-sliding, UV-resistant and freeze-thaw resistant layer contains peat soil, modified plant fiber, UV-resistant and freeze-thaw resistant composite material and polyethylene glycol. This technology primarily targets ecological slope protection in high-altitude, cold, and humid regions. Its technical solutions emphasize freeze-thaw resistance and UV resistance, but do not address the erosion resistance of steep slopes under heavy rainfall conditions. Furthermore, its anti-sliding, UV-resistant, and freeze-thaw resistant layer still contains 100-200 parts by weight of peat moss, thus relying on natural peat moss resources. It also lacks a long-term nutrient release mechanism and does not utilize urban solid waste such as waste concrete as a skeletal material. Chinese invention patent CN119349945B (authorization announcement date March 4, 2025) relates to green prefabricated slope vegetation protection technology, characterized by prefabricated components and prefabricated construction, including green prefabricated rib protection and green prefabricated frame beams. In terms of protection and other forms, this technology focuses on the prefabricated construction of slope protection components, mainly addressing the issue of green construction level in slope protection. It belongs to the field of slope protection engineering and does not involve technical issues such as the erosion resistance design of cover materials, nutrient slow release, and plant compatibility. The technical solution is fundamentally different from this application. In addition, Chinese invention patent CN102515934B (authorization announcement date April 9, 2014) discloses γ-polyglutamic acid mixed fertilizer and its application in desert management. It utilizes the water retention capacity and slow release effect of γ-polyglutamic acid to improve the survival rate of desert xerophytic plants, but it is applied to desert (arid areas) rather than steep rock slopes and does not involve chemical mineralization cementation and erosion resistance design.
[0005] In summary, none of the existing technologies mentioned above have designed material systems to address the erosion resistance requirements of steep slopes under heavy rainfall conditions. The technical problems of existing soil covering materials for steep slopes in terms of erosion resistance, long-term slow release of nutrients, plant compatibility, and low-carbon preparation still need to be solved. Summary of the Invention
[0006] The following unresolved technical problems exist with existing topsoil materials for steep slopes: 1) Using cement, lime, or alkali-activated industrial solid waste as cementing materials results in excessively high alkalinity (pH>11), inhibiting plant seed germination and root penetration, and the hydration products are brittle and prone to cracking; 2) Conventional organic fibers and inorganic matrices only have physical friction and lack chemical bonding, resulting in a sharp decline in reinforcement effect over time; 3) Fertilizers are mostly fast-acting chemical fertilizers directly mixed in, and nutrients are largely leached away by rainwater 3-6 months after topsoiling, leading to nutrient deficiency and vegetation decline in the later stages; 4) The resource utilization rate of urban solid waste such as waste concrete is low, and the preparation process often requires high-temperature hot melting (>160℃) or steam curing, resulting in high energy consumption.
[0007] The technical problem to be solved by the present invention is to address the defects in the above-mentioned prior art by providing a high-steep slope soil for soil stabilization and conservation, and its preparation method, which is completely independent of cement / alkali-activated materials, natural fibers and peat, does not require high-temperature hot melting, and has excellent erosion resistance, long-term slow-release fertilization capacity and suitable plant growth environment.
[0008] To address the aforementioned technical problems, this invention provides a reconstructed soil for stabilizing and protecting steep slopes, comprising the following components by weight:
[0009] 45-65 parts of recycled fine aggregate from waste concrete, 8-16 parts of lithium magnesium silicate, 6-14 parts of polyvinylpyrrolidone-borax double-network hydrogel dry powder, 5-12 parts of urea phosphate, 4-10 parts of calcium nitrate tetrahydrate, 2-6 parts of ammonium bicarbonate, 0.5-3 parts of γ-polyglutamic acid, and 25-40 parts of water.
[0010] The urea phosphate reacts in situ with the calcium nitrate tetrahydrate in the reconstructed soil to generate hydroxyapatite microcrystals, which bind the recycled fine aggregate from the waste concrete.
[0011] The lithium magnesium silicate forms an organic-inorganic interpenetrating network with the polyvinylpyrrolidone-borax dual-network hydrogel.
[0012] The ammonium bicarbonate decomposes and foams during the mixing process, causing the material volume to expand significantly, the internal bubbles to be evenly distributed, and the surface to appear as a fine foam, forming interconnected pores inside the reconstructed soil.
[0013] The waste concrete recycled fine aggregate has a particle size of 1.0~3.0mm, a crushing index of ≤20%, a water absorption rate of ≤6%, and a mud content of ≤1.5%.
[0014] The 2% aqueous suspension of the magnesium lithium silicate has a viscosity ≥1000 mPa·s and a pH of 9.0~9.5.
[0015] The polyvinylpyrrolidone-borax dual-network hydrogel dry powder has a polyvinylpyrrolidone to borax mass ratio of 15:1, a water absorption ratio of 25 to 45 times, and a compression elastic recovery rate of ≥85%.
[0016] The molecular weight of the γ-polyglutamic acid is 700,000 to 800,000 Da.
[0017] The reconstructed soil has a dry density of 0.70~0.95g / cm³, a saturated compressive strength ≥1.2MPa, a 2h erosion loss rate ≤6.5% under a slope of 55° and a rainfall of 120mm / h, a 28d cumulative nitrogen and phosphorus release rate ≤40%, and a pH value of 6.5~7.8.
[0018] This invention also provides a method for preparing the above-mentioned reconstructed soil, comprising the following steps:
[0019] S01: Weigh each component according to the proportion;
[0020] S02: Mix γ-polyglutamic acid with a first part by weight of water to prepare a pre-solution; mix ammonium bicarbonate with a second part by weight of water to prepare a suspension; the sum of the first part by weight of water and the first part by weight of water is equal to the total amount of water weighed in S01;
[0021] S03: The waste concrete recycled fine aggregate, lithium magnesium silicate, polyvinylpyrrolidone-borax double network hydrogel dry powder, urea phosphate, and calcium nitrate tetrahydrate are put into a mixer and dry-mixed to obtain a dry-based mixture.
[0022] S04: Add γ-polyglutamic acid pre-solution to the dry base mixture and mix wet, then add ammonium bicarbonate suspension and stir at 15~25 r / min for 1~3 min until the material volume expands significantly, the internal bubbles are evenly distributed, and the surface shows a fine foam. Control the material temperature not to exceed 25℃ to obtain foamed plastic mixture.
[0023] S05: Mold the foamed plastic mixture, let it stand until it initially sets, cover it with a moisture-retaining material, and cure it in an environment of 10~30℃ and relative humidity ≥70% until it solidifies, thus obtaining the reconstructed soil.
[0024] In step S03, the dry mixing speed is 20~35 r / min and the time is 4~8 min; in step S04, the wet mixing speed is 25~40 r / min and the time is 3~5 min, and the foaming mixing speed is 15~25 r / min and the time is 1~3 min; in step S05, the molding is carried out by static pressure or light vibration, the compaction pressure is ≤2MPa, and the curing time is 5~8 days.
[0025] The present invention also provides the application of the above-mentioned reconstructed soil in the soil covering reconstruction and ecological restoration of mine rock slopes, spoil heaps or quarry waste sites with a slope of ≥45°.
[0026] Apply a layer of 20-40cm thickness, and then sow or spray drought-resistant and barren-tolerant native plant seeds on the surface. The plant seeds include one or more of Vitex negundo, Magnolia multiflora, Bromus spp., and Zoysia japonica, with a sowing rate of 30-50g / m².
[0027] The following technical features of this application are not disclosed in the prior art: using recycled fine aggregate from waste concrete as a skeleton to replace natural sand and gravel; using lithium magnesium silicate and polyvinylpyrrolidone-borax dual-network hydrogel to form an organic-inorganic interpenetrating network; using ammonium bicarbonate in a weakly alkaline system for controlled decomposition and in-situ foaming to form interconnected pores; using urea phosphate and calcium nitrate tetrahydrate to generate hydroxyapatite microcrystals in situ to achieve chemical mineralization and slow release of nitrogen and phosphorus; adding γ-polyglutamic acid as a root promoter; and integrating room temperature foaming, gelation, and in-situ consolidation into a single process.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. Excellent erosion resistance: The dry density of the reconstructed soil of this invention is 0.70~0.95g / cm³, the saturated compressive strength is ≥1.2MPa, and the erosion loss rate is ≤6.5% after 2 hours under the conditions of 55° slope and 120mm / h rainfall. This effect is due to the high elastic recovery ability of the material given by the organic-inorganic interpenetrating network formed by lithium magnesium silicate and hydrogel, the density reduction by ammonium bicarbonate foaming, and the in-situ cementing effect of hydroxyapatite.
[0030] 2. Long-term slow-release nutrient supply capacity: The cumulative release rate of nitrogen and phosphorus in the reconstructed soil is ≤40% in 28 days, and the slow-release period is ≥8 months. Through the dual mechanism of urea phosphate hydrolysis slow release and hydroxyapatite adsorption, long-term nutrient supply is achieved, overcoming the defect of existing fast-acting fertilizers that are lost in large quantities by rainwater 3-6 months after covering with soil.
[0031] 3. Plant-friendly: The system pH value is controlled at 6.5~7.8, the germination rate of alfalfa is 88%~94%, and the shear strength of the root-soil interface is ≥28kPa, which overcomes the defect of existing cement-based materials that inhibit plant growth due to high alkalinity (pH>11).
[0032] 4. Solid waste and low-carbon preparation: The main skeleton is recycled fine aggregate from waste concrete (accounting for more than 45% of dry materials), without the use of natural topsoil and peat; it is prepared at room temperature (≤25℃), without the need for high-temperature hot melting or steam curing, reducing raw material costs by more than 65% and energy consumption by more than 75%. Attached Figure Description
[0033] Figure 1 A flowchart illustrating the preparation process of reconstructed soil for soil stabilization and conservation on steep slopes, as provided in an embodiment of the present invention. Detailed Implementation
[0034] The technical solution of the present invention will be described in detail below. The described embodiments are only some embodiments of the present invention, and not all embodiments.
[0035] Based on the embodiments of the present invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] This invention discloses a reconstructed soil for stabilizing and protecting steep slopes, comprising the following components by weight: 45-65 parts of recycled fine aggregate from waste concrete, 8-16 parts of lithium magnesium silicate, 6-14 parts of polyvinylpyrrolidone-borax dual-network hydrogel powder, 5-12 parts of urea phosphate, 4-10 parts of calcium nitrate tetrahydrate, 2-6 parts of ammonium bicarbonate, 0.5-3 parts of γ-polyglutamic acid, and 25-40 parts of water. The urea phosphate and calcium nitrate tetrahydrate react in situ in the reconstructed soil to generate hydroxyapatite microcrystals, which bind the recycled fine aggregate from waste concrete. The lithium magnesium silicate and the polyvinylpyrrolidone-borax dual-network hydrogel form an organic-inorganic interpenetrating network. The ammonium bicarbonate decomposes and foams during mixing, forming interconnected pores within the reconstructed soil.
[0037] The waste concrete recycled fine aggregate has a particle size of 1.0~3.0mm, a crushing index of ≤20%, a water absorption rate of ≤6%, and a mud content of ≤1.5%.
[0038] The 2% aqueous suspension of lithium magnesium silicate has a viscosity ≥1000 mPa·s and a pH of 9.0~9.5; the polyvinylpyrrolidone-borax dual-network hydrogel dry powder has a mass ratio of polyvinylpyrrolidone to borax of 15:1, a water absorption ratio of 25~45 times, and a compression elastic recovery rate ≥85%.
[0039] The molecular weight of the γ-polyglutamic acid is 700,000 to 800,000 Da.
[0040] The reconstructed soil has a dry density of 0.70~0.95g / cm³, a saturated compressive strength ≥1.2MPa, a 2h erosion loss rate ≤6.5% under a slope of 55° and a rainfall of 120mm / h, a 28d cumulative nitrogen and phosphorus release rate ≤40%, and a pH value of 6.5~7.8.
[0041] The specifications and pretreatment methods of the raw materials used in the following examples and comparative examples are as follows:
[0042] Waste concrete recycled fine aggregate: Waste concrete is crushed, screened (screen size is 0.5mm, 1.0mm, 3.0mm and 4.0mm respectively), washed with water to remove fine powder, and dried at 105℃ to constant weight to obtain aggregates with different particle size ranges. The preferred particle size is 1.0~3.0mm, crushing index is 18%, water absorption rate is 5.2%, and mud content is 1.2%.
[0043] Lithium magnesium silicate: a synthetic layered silicate with a viscosity of 1100 mPa·s in a 2% aqueous suspension and a pH of 9.2.
[0044] Polyvinylpyrrolidone (PVP): K90, molecular weight 1.2 million, purity ≥99%.
[0045] Borax: Industrial grade sodium tetraborate decahydrate, purity ≥99%, fineness ≥200 mesh.
[0046] Urea phosphate: Industrial grade, total nitrogen ≥17.5%, phosphorus pentoxide ≥44.5%, pH 1.8.
[0047] Calcium nitrate tetrahydrate: Industrial grade, calcium nitrate content ≥98.5%, particle size ≤0.5mm.
[0048] Ammonium bicarbonate: food grade, purity ≥99.5%, fineness ≥80 mesh.
[0049] γ-Polyglutamic acid: a microbial fermentation product with a molecular weight of 750,000 Da and a purity of ≥92%.
[0050] Polyvinylpyrrolidone-borax dual-network hydrogel powder:
[0051] S11: Take 150g of PVP and 10g of borax (mass ratio 15:1), add 2000mL of deionized water, stir to dissolve, adjust the pH to 9.0 with 1mol / L NaOH, and crosslink at room temperature for 4h.
[0052] S12: Pour the cross-linked gel into a tray (1~2cm thick), freeze at -20℃ for 24h, then transfer to a freeze dryer and freeze dry under vacuum at -50℃ for 48h.
[0053] S13: Take out the freeze-dried block, crush it with a high-speed pulverizer, pass it through an 80-mesh sieve to obtain porous particles, seal and store it. The porous particles have a water absorption ratio of 38 times and a compression elastic recovery rate of 92%.
[0054] Unless otherwise specified, all other raw materials are industrial-grade qualified products.
[0055] The following embodiments illustrate a method for preparing reconstructed soil for soil stabilization and conservation on steep slopes, comprising the following steps:
[0056] S01: Weigh each component according to the proportion;
[0057] S02: Prepare a pre-solution of γ-polyglutamic acid with water, and prepare a suspension of ammonium bicarbonate with the remaining water;
[0058] S03: Dry-mix waste concrete recycled fine aggregate, lithium magnesium silicate, polyvinylpyrrolidone-borax dual-network hydrogel dry powder, urea phosphate, and calcium nitrate tetrahydrate to obtain a dry-based mixture.
[0059] S04: Add γ-polyglutamic acid pre-solution to the dry base mixture and mix wet, then add ammonium bicarbonate suspension and stir at 15~25 r / min for 1~3 min until the material volume expands significantly, the internal bubbles are evenly distributed, and the surface shows a fine foam. Control the material temperature not to exceed 25℃ to obtain foamed plastic mixture.
[0060] S05: Mold the foamed plastic mixture, let it stand until it initially sets, cover it with a moisture-retaining material, and cure it in an environment of 10~30℃ and relative humidity ≥70% until it solidifies, thus obtaining the reconstructed soil.
[0061] In step S03, the dry mixing speed is 20~35 r / min and the time is 4~8 min;
[0062] In step S04, the wet mixing speed is 25~40 r / min and the time is 3~5 min, and the foaming mixing speed is 15~25 r / min and the time is 1~3 min;
[0063] In step S05, the molding process uses static pressure or light vibration, with a compaction pressure ≤2MPa and a curing time of 5~8 days.
[0064] The realization of the "in-situ reaction of urea phosphate and calcium nitrate tetrahydrate to generate hydroxyapatite microcrystals" described in this invention is based on the following synergistic mechanism: 1) Feeding sequence and local pH control: Urea phosphate (1% aqueous solution pH≈1.89) and calcium nitrate tetrahydrate are pre-dry mixed to ensure uniform contact at the particle scale; after adding γ-polyglutamic acid pre-solution during the wet mixing stage, the water film first dissolves urea phosphate and calcium nitrate tetrahydrate, forming a locally supersaturated solution of Ca²⁺ and phosphate in the micro-regions on the surface of aggregate particles; finally, the added ammonium bicarbonate suspension acts as a slow-release alkali source, and the NH3 produced by its decomposition slowly raises the pH of the system from acidic to weakly alkaline (final pH...). 1) pH 6.5~7.8), providing suitable conditions for the nucleation and growth of hydroxyapatite; 2) Dual function of ammonium bicarbonate: In this invention, ammonium bicarbonate acts as both a foaming agent (decomposing to produce CO2 and NH3, forming interconnected pores) and a slow-release alkali source (the NH3 produced by its decomposition combines with water to generate NH4OH, slowly increasing the pH of the system); 3) Buffering and template function of lithium magnesium silicate: The colloidal network of lithium magnesium silicate (2% aqueous suspension, pH 9.0~9.5) has buffering capacity to smooth local pH fluctuations; its nanolayered structure helps promote the crystallization of hydroxyapatite and lowers the nucleation energy barrier; 4) Thermodynamic feasibility: Hydroxyapatite has an extremely low solubility product constant, and when Ca²⁺ and PO₄³⁻ reach a certain concentration, the precipitation reaction is thermodynamically strongly favorable; in this system, urea phosphate hydrolysis continuously releases PO₄³⁻, and calcium nitrate tetrahydrate provides Ca²⁺, under weakly alkaline conditions (pH 6.5~7.8), the precipitation reaction is thermodynamically favorable; (7~9), the ion product of Ca²⁺ and PO₄³⁻ is sufficient to satisfy the thermodynamic conditions for hydroxyapatite precipitation.
[0065] Example 1
[0066] A type of reconstructed soil for stabilizing and protecting high and steep slopes, comprising the following components by weight: 55 parts of recycled fine aggregate from waste concrete (particle size 1.0~3.0mm), 12 parts of lithium magnesium silicate, 10 parts of polyvinylpyrrolidone-borax double-network hydrogel dry powder, 8 parts of urea phosphate, 7 parts of calcium nitrate tetrahydrate, 4 parts of ammonium bicarbonate, 1.5 parts of γ-polyglutamic acid, and 32 parts of water.
[0067] The preparation flowchart of this embodiment is as follows: Figure 1 As shown, its preparation method includes the following steps:
[0068] S01: Weigh each component according to the above weight proportions.
[0069] S02: Mix 1.5 kg of γ-polyglutamic acid with 7.5 kg (as the first part by weight, accounting for about 23.4% of the total water of 32 kg), stir and dissolve to prepare a γ-polyglutamic acid pre-solution; mix 4 kg of ammonium bicarbonate with 24.5 kg (as the second part by weight, accounting for 76.6% of the total water, the sum of the first and second parts by weight is 32 parts of the total water), stir to form a suspension, and prepare and use immediately.
[0070] S03: Add 55kg of recycled fine aggregate, 12kg of lithium magnesium silicate, 10kg of polyvinylpyrrolidone-borax double network hydrogel dry powder, 8kg of urea phosphate, and 7kg of calcium nitrate tetrahydrate into a forced mixer (model SJD-50) and dry mix at 30r / min for 6min to obtain a dry-based mixture.
[0071] S04: Add γ-polyglutamic acid pre-solution to the dry base mixture and wet mix at 35 r / min for 4 min to fully hydrate lithium magnesium silicate to form a gel that coats the aggregate particles; then slowly add ammonium bicarbonate suspension and continue stirring at 20 r / min until the material volume expands significantly, the internal bubbles are evenly distributed, and the surface shows a fine foam (foaming stirring time is about 2 min). The actual temperature of the material during the stirring process is 23℃, and a foamed plastic mixture is obtained.
[0072] S05: Immediately fill the foamed plastic mixture into a 100mm×100mm×100mm cubic mold and perform static pressing (pressure 1.5MPa, holding pressure for 30s). After molding, let it stand for 3 hours until the mixture initially sets (the surface does not collapse when pressed with a finger). Cover it with non-woven fabric and transfer it to a curing room. Cure it for 6 days at 20℃ and 75% relative humidity. During the curing period, spray it with mist water once every 48 hours, with a spraying amount of 0.4L / m² each time. After curing, demold it to obtain the reconstructed soil test block for soil stabilization and conservation of steep slopes.
[0073] Example 2
[0074] The difference between this embodiment and Embodiment 1 lies in the adjustment of the formula and some process parameters, as detailed below:
[0075] Weigh the following components by weight: 50 parts of recycled fine aggregate from waste concrete, 15 parts of lithium magnesium silicate, 8 parts of polyvinylpyrrolidone-borax double-network hydrogel dry powder, 10 parts of urea phosphate, 5 parts of calcium nitrate tetrahydrate, 5 parts of ammonium bicarbonate, 2 parts of γ-polyglutamic acid, and 35 parts of water.
[0076] The preparation method differs from that in Example 1 in that:
[0077] S03 dry mixing speed 25r / min, time 5min;
[0078] S04 wet mixing speed 30r / min, time 5min, foaming mixing speed 18r / min, time 3min, material temperature 22℃;
[0079] S05 requires a curing temperature of 18℃ and a curing time of 7 days.
[0080] Example 3
[0081] The difference between this embodiment and Example 1 is that the formula uses a lower value and the foaming agent is higher, as follows: By weight, the following components are weighed: 60 parts of waste concrete recycled fine aggregate, 10 parts of lithium magnesium silicate, 12 parts of polyvinylpyrrolidone-borax double network hydrogel dry powder, 6 parts of urea phosphate, 8 parts of calcium nitrate tetrahydrate, 3 parts of ammonium bicarbonate, 1 part of γ-polyglutamic acid, and 28 parts of water.
[0082] The preparation method differs from that in Example 1 in that:
[0083] S05 is formed by light vibration (excitation force 5kN, frequency 30Hz, time 20s), curing temperature 25℃, curing time 5 days.
[0084] Example 4
[0085] The difference between this embodiment and Example 1 is that the formulation uses a higher value and the proportion of hydrogel is higher, as detailed below:
[0086] The following components are weighed by weight: 48 parts of recycled fine aggregate from waste concrete, 14 parts of lithium magnesium silicate, 13 parts of polyvinylpyrrolidone-borax double-network hydrogel dry powder, 11 parts of urea phosphate, 9 parts of calcium nitrate tetrahydrate, 5.5 parts of ammonium bicarbonate, 2.5 parts of γ-polyglutamic acid, and 38 parts of water.
[0087] The preparation method differs from that in Example 1 in that:
[0088] S04 foaming and stirring time: 2.5 min;
[0089] S05 curing temperature 22℃, curing time 6 days, other conditions are the same as in Example 1.
[0090] Example 5
[0091] The difference between this embodiment and Embodiment 1 is that static pressure compaction is eliminated, and natural flow molding is adopted, as detailed below:
[0092] The formula in this embodiment is the same as that in Example 1, but the preparation method differs from that in Example 1 in the following ways:
[0093] In S05, the mixture is poured directly into the mold without applying any pressure, relying solely on its own weight for leveling and foaming expansion to form the final product.
[0094] Example 6
[0095] To verify the preferred process parameters of the present invention, the following preferred formulation and process are used in this embodiment:
[0096] The following components are weighed by weight: 52 parts of recycled fine aggregate from waste concrete (particle size 1.0~3.0mm, crushing index 18%, water absorption 5.2%), 13 parts of lithium magnesium silicate (2% suspension viscosity 1100mPa·s, pH 9.2), 11 parts of polyvinylpyrrolidone-borax dual-network hydrogel dry powder (PVP:borax = 15:1, water absorption ratio 38 times), 9 parts of urea phosphate, 6 parts of calcium nitrate tetrahydrate, 4.5 parts of ammonium bicarbonate, 2 parts of γ-polyglutamic acid (molecular weight 750,000 Da), and 33 parts of water.
[0097] The preparation method differs from that in Example 1 in that:
[0098] S03 dry mixing speed 28r / min, time 7min;
[0099] S04 wet mixing speed 32r / min, time 4min, foaming mixing speed 22r / min, time 2min, material temperature 24℃;
[0100] S05 is formed by static pressure (pressure 1.2MPa), with a curing temperature of 22℃, relative humidity of 80%, and a curing time of 6 days. 0.3L / m² of mist water is sprayed every 48 hours.
[0101] Comparative Example 1
[0102] The difference from Example 1 is that lithium magnesium silicate is not added, and water is used instead in equal parts by weight. The remaining components and preparation methods are the same as in Example 1.
[0103] Comparative Example 2
[0104] The difference from Example 1 is that an equal weight of polyvinylpyrrolidone-borax dual-network hydrogel powder is replaced with ordinary polyacrylamide water-retaining agent (non-crosslinked, water absorption ratio of 120 times), and the rest is the same as in Example 1.
[0105] Comparative Example 3
[0106] The difference from Example 1 is that ammonium bicarbonate is not added, and water is used instead in equal parts by weight; otherwise, it is the same as Example 1.
[0107] Comparative Example 4
[0108] The difference from Example 1 is that urea phosphate is replaced with an equal weight mixture of ordinary urea and potassium dihydrogen phosphate (N and P content is similar to that of urea phosphate, and the mass ratio of urea to potassium dihydrogen phosphate is 1:1.2), and the rest is the same as in Example 1.
[0109] Comparative Example 5
[0110] The difference from Example 1 is that calcium nitrate tetrahydrate is not added, and water is used instead in equal parts by weight; otherwise, it is the same as Example 1.
[0111] Comparative Example 6
[0112] The commonly used commercially available mine slope greening substrate is used. Its main components are: 55% garden soil, 15% peat, 8% ordinary silicate cement (P.O42.5), 1.5% polypropylene fiber (12mm in length), 1.2% sodium polyacrylate water-retaining agent, 4% compound fertilizer (15-15-15), and the remainder is water.
[0113] Mixing, molding, and natural curing for 28 days are carried out in the conventional manner.
[0114] Performance testing methods
[0115] The test blocks (100mm×100mm×100mm) prepared in Examples 1-6 and Comparative Examples 1-6 were subjected to the following performance tests. Three parallel samples were used in each group, and the arithmetic mean was taken.
[0116] Dry density: Dry the test block at 105℃ to constant weight, measure the volume, and calculate the dry density (g / cm³).
[0117] Saturated compressive strength: The cured specimen was immersed in deionized water for 48 hours. Immediately after removal, it was tested using a hydraulic universal testing machine (WDW-100E type) with a loading rate of 0.5 mm / min. The failure load was recorded, and the compressive strength (MPa) was calculated.
[0118] Saturated water holding capacity: The test block was dried at 105℃ to constant weight to obtain dry mass m0. After soaking in water for 48 hours, it was taken out and the surface moisture was wiped off with a damp cloth. The saturated wet mass m1 was obtained. Water holding capacity (%) = (m1-m0) / m0×100%.
[0119] Erosion loss rate: The test block cured for 28 days was cut into 100mm×100mm×50mm thin slices and placed on an adjustable slope test platform, with the slope adjusted to 55°. An artificial simulated rainfall system (rainfall intensity 120mm / h, duration 2h) was used to collect the eroded solids, which were dried at 105℃ and weighed. The loss rate (%) was calculated as: loss dry mass / total dry mass of the test block × 100%.
[0120] Nutrient release rate: Take 10g of sample (the test blocks of the examples and comparative examples were crushed and passed through a 2mm sieve) and soak them in 100mL of deionized water. Take samples on days 1, 3, 7, 14, 21 and 28 respectively. Nitrogen release is determined by the p-dimethylaminobenzaldehyde colorimetric method and phosphorus release is determined by the molybdenum antimony colorimetric method. Calculate the cumulative release rate (%).
[0121] Plant germination rate: Alfalfa seeds (30 seeds / 400cm²) were evenly sown on the surface of the test block (200mm×200mm×50mm) after 7 days of cultivation. The block was covered with 1cm of fine soil of the same substrate and cultivated in a greenhouse at 20~25℃ with the soil kept moist. The germination rate (%) was calculated after 7 days.
[0122] Shear strength of the root-soil interface: φ150mm×100mm cylindrical specimens were prepared with a φ8mm hole pre-drilled in the center. Alfalfa seedlings (root length about 4~5cm) that had been pre-cultured for 7 days were transplanted and fixed with the same substrate. After culturing in a greenhouse for 90 days, the shear strength (kPa) of the root-soil interface was measured using a miniature vane shear tester at a shear rate of 2mm / min.
[0123] The performance test results of Examples 1-6 and Comparative Examples 1-6 are summarized in Table 1.
[0124] Table 1 Performance test results of Examples 1-6 and Comparative Examples 1-6
[0125] Sample number Dry density (g / cm³) Saturated strength (MPa) Saturated water holding capacity (%) 2-hour flushing rate (%) 28-day cumulative nitrogen release rate (%) 28-day phosphorus release rate (%) Alfalfa germination rate (%) 90-day root-soil shear strength (kPa) Example 1 0.85 1.68 88.5 5.6 35.2 33.8 91 29.3 Example 2 0.78 1.52 91.2 5.1 38.6 36.5 93 31.8 Example 3 0.92 1.85 85.6 6.2 32.1 30.9 88 27.6 Example 4 0.88 1.72 87.3 5.8 36.8 35.2 90 28.5 Example 5 0.62 0.95 94.2 12.3 37.5 35.8 86 18.2 Example 6 0.82 1.77 89.6 5.3 33.5 32.1 94 30.6 Comparative Example 1 0.92 0.68 72.3 28.6 88.2 85.6 54 9.5 Comparative Example 2 0.88 1.12 79.5 18.4 36.8 34.9 78 15.3 Comparative Example 3 1.15 1.85 63.2 9.8 34.5 32.8 71 25.8 Comparative Example 4 0.86 1.58 87.6 6.2 82.4 79.3 85 28.1 Comparative Example 5 0.84 1.02 86.8 8.9 36.2 34.5 82 21.3 Comparative Example 6 1.28 0.82 48.5 36.2 92.5 89.8 58 7.6
[0126] Results Analysis
[0127] As shown in Table 1, the reconstructed soils for high and steep slope stabilization and conservation prepared in Examples 1-6 have the following properties: dry density of 0.78-0.92 g / cm³ (0.62 g / cm³ in Example 5 after natural flow molding); saturated compressive strength of 1.52-1.85 MPa (0.95 MPa in Example 5); saturated water holding capacity of 85.6%-94.2%; and 2-hour erosion loss rate of 5.1%-6.2% (only 12.3% in Example 5). The reconstructed soil significantly outperformed all comparative studies in key indicators, including a 28-day cumulative nitrogen release rate of 32.1%–38.6%, a 28-day cumulative phosphorus release rate of 30.9%–36.5%, an alfalfa germination rate of 86%–94%, and a 90-day root-soil shear strength of 18.2–31.8 kPa. Under cement-free and heat-free curing conditions, the reconstructed soil achieved a saturated compressive strength of 1.52–1.85 MPa, with a 2-hour erosion loss rate of only 5.1%–6.2%. These mechanical properties are solely attributed to the synergistic cementing effect of in-situ generated hydroxyapatite microcrystals and the lithium magnesium silicate-hydrogel interpenetrating network.
[0128] It is worth noting that even when compaction was completely eliminated in Example 5, its scour loss rate (12.3%) was still much lower than that of the commercially available product in Comparative Example 6 (36.2%), demonstrating the inherent scour resistance of the formulation system of the present invention; and by applying slight compaction (Examples 1-4, 6), the loss rate further dropped sharply to 5.1%-6.2%, demonstrating the synergistic promoting effect of pressure parameters on the construction of efficient interpenetrating networks and mineralized cementation.
[0129] Example 6 exhibits the best overall performance, with a saturated compressive strength of 1.77 MPa, a 2-hour erosion loss rate of only 5.3%, a 28-day cumulative nitrogen and phosphorus release rates of 33.5% and 32.1%, respectively, an alfalfa germination rate of 94%, and a 90-day root-soil shear strength of 30.6 kPa. Compared with the commercially available product in Comparative Example 6, the shear strength is increased by approximately 302%, and the erosion loss rate is reduced by approximately 85%.
[0130] Compared with the absence of magnesium lithium silicate in Comparative Example 1, the saturated compressive strength dropped to 0.68 MPa, the 2-hour scouring loss rate was as high as 28.6%, the germination rate of alfalfa was only 54%, and the root-soil shear strength was only 9.5 kPa after 90 days. This is because the absence of magnesium lithium silicate prevented the formation of an inorganic cementitious skeleton, resulting in a lack of effective bonding between aggregate particles and the inability of the mixture to form an integral structure. At the same time, the increased pH of the system inhibited seed germination.
[0131] In Comparative Example 2, when ordinary polyacrylamide water-retaining agent was used to replace the double-network hydrogel, the saturated compressive strength decreased to 1.12 MPa, the 2-hour scouring loss rate increased to 18.4%, and the 90-day root-soil shear strength was only 15.3 kPa. Ordinary polyacrylamide has a linear molecular structure and lacks the high elastic recovery ability brought by double-network cross-linking. After absorbing water and swelling, it cannot buffer the shear stress generated by water scouring and is easily lost with water, resulting in a significant decrease in structural stability.
[0132] Comparative Example 3, without ammonium bicarbonate foaming, had a dry density as high as 1.15 g / cm³, a saturated water holding capacity of only 63.2%, and a germination rate of alfalfa dropped to 71%. The unfoamed mixture lacked interconnected pores, had a high material density, little water storage space, made it difficult for roots to penetrate, and increased its own weight load, which was not conducive to the stability of steep slopes.
[0133] In Comparative Example 4, urea phosphate was replaced with ordinary urea + potassium dihydrogen phosphate. Although the leaching loss rate of 6.2% was close to that of the example, the cumulative release rates of nitrogen and phosphorus after 28 days were as high as 82.4% and 79.3%, respectively, indicating rapid nutrient leaching. Ordinary fast-acting fertilizers do not have a slow-release mechanism and cannot meet the medium- and long-term nutrient needs of vegetation. However, this invention achieves a long-term supply of nitrogen and phosphorus through the hydrolytic slow release of urea phosphate and the adsorption of phosphate by hydroxyapatite.
[0134] Comparative Example 5, without calcium nitrate tetrahydrate, showed a saturated compressive strength reduced to 1.02 MPa, a 2-hour scouring loss rate increased to 8.9%, and a 90-day root-soil shear strength of only 21.3 kPa. The lack of calcium source prevented the formation of hydroxyapatite microcrystals, resulting in the absence of in-situ chemical bonding between aggregate particles. At the same time, the chelating effect of γ-polyglutamic acid could not be fully utilized, weakening the anchoring capacity of the root-soil interface.
[0135] Compared with the conventional commercially available mine slope greening substrate in Example 6, all indicators were significantly inferior to those of the embodiments of the present invention. Its dry density was as high as 1.28 g / cm³, its saturated water holding capacity was only 48.5%, its 2-hour scouring loss rate was as high as 36.2%, its 28-day nitrogen and phosphorus release rates were both over 89%, its alfalfa germination rate was only 58%, and its 90-day root-soil shear strength was only 7.6 kPa. The commercially available products use cement as a binder, which has high alkalinity, high brittleness, poor water retention, and rapid nutrient loss. They are completely unable to meet the long-term ecological restoration needs of steep slopes (slope ≥ 45°) under heavy rainfall conditions.
[0136] In summary, this invention achieves significantly superior technical effects compared to existing technologies in terms of lightweight, high strength, high water retention, erosion resistance, slow nutrient release, and plant affinity through the synergistic combination of an organic-inorganic interpenetrating network formed by lithium magnesium silicate and polyvinylpyrrolidone-borax dual-network hydrogel, interconnected pores constructed by in-situ chemical foaming of ammonium bicarbonate, microcrystalline mineralization cementation of hydroxyapatite generated in-situ by urea phosphate and calcium nitrate tetrahydrate, and the root-promoting and water-retaining effects of γ-polyglutamic acid.
[0137] Field application examples
[0138] An experimental site with an area of 500 m² was selected on the slope of a spoil heap in an open-pit iron mine (slope of 50°, slope height of 30 m, rock type of granite waste stockpile, average annual temperature of 7.0℃, annual rainfall of 550 mm).
[0139] Using the formula and preparation method of Example 6, a horizontal forced mixer was set up on site to prepare foamed plastic mixture. After it was compacted by light vibration (excitation force 5kN, frequency 30Hz), the thickness was spread to 30cm, the surface was covered with non-woven fabric, and it was cured in a simple greenhouse for 7 days (temperature 15~25℃, water sprayed once in the morning and once in the evening).
[0140] After maintenance, sow a mixture of seeds (Vitex negundo: Magnolia multiflora: Bromus spp.: Zoysia japonica = 2:2:3:3) at a rate of 40g / m², and cover with a thin layer of fine soil.
[0141] The results showed that the germination rate was 91% in 28 days, the vegetation coverage was 89% in 90 days, and the coverage reached 97% in 180 days.
[0142] After the first full rainy season following construction (June to September of that year, during which the maximum single rainfall was 85 mm / 24h), there were no obvious scouring gullies or spalling on the slope. Random sampling measured the average shear strength of the root-soil composite to be 27.8 kPa, and the vegetation survival rate was 94%.
[0143] The control area (200m²) that was restored using commercially available products in the same site showed that after overwintering, the vegetation coverage dropped to 38%, and multiple longitudinal cracks (2-5mm wide) and local spalling appeared on the slope. The shear strength of the root-soil interface was only 6.5kPa.
[0144] Field applications have shown that the soil reconstructed by this invention has excellent mechanical stability, erosion resistance, and ecological restoration effects, making it suitable for large-scale ecological restoration projects on steep slopes.
Claims
1. A type of reconstructed soil for soil stabilization and conservation on steep slopes, characterized in that, The material is composed of the following components in parts by weight: 45-65 parts of recycled fine aggregate from waste concrete, 8-16 parts of lithium magnesium silicate, 6-14 parts of polyvinylpyrrolidone-borax dual-network hydrogel dry powder, 5-12 parts of urea phosphate, 4-10 parts of calcium nitrate tetrahydrate, 2-6 parts of ammonium bicarbonate, 0.5-3 parts of γ-polyglutamic acid, and 25-40 parts of water. The urea phosphate and calcium nitrate tetrahydrate react in situ in the reconstructed soil to generate hydroxyapatite microcrystals, which bind the recycled fine aggregate from waste concrete. The lithium magnesium silicate and the polyvinylpyrrolidone-borax dual-network hydrogel form an organic-inorganic interpenetrating network. The ammonium bicarbonate decomposes and foams during mixing, forming interconnected pores within the reconstructed soil.
2. The reconstructed soil for soil stabilization and conservation on steep slopes according to claim 1, characterized in that, The waste concrete recycled fine aggregate has a particle size of 1.0~3.0mm, a crushing index of ≤20%, a water absorption rate of ≤6%, and a mud content of ≤1.5%.
3. The reconstructed soil for soil stabilization and conservation on steep slopes according to claim 1, characterized in that, The 2% aqueous suspension of the magnesium lithium silicate has a viscosity ≥1000 mPa·s and a pH of 9.0~9.5; the polyvinylpyrrolidone-borax dual-network hydrogel dry powder has a mass ratio of polyvinylpyrrolidone to borax of 15:1, a water absorption ratio of 25~45 times, and a compression elastic recovery rate ≥85%.
4. The reconstructed soil for soil stabilization and conservation on steep slopes according to claim 1, characterized in that, The molecular weight of the γ-polyglutamic acid is 700,000 to 800,000 Da.
5. The reconstructed soil for soil stabilization and conservation on steep slopes according to claim 1, characterized in that, The reconstructed soil has a dry density of 0.70~0.95g / cm³, a saturated compressive strength ≥1.2MPa, a 2h erosion loss rate ≤6.5% under a slope of 55° and a rainfall of 120mm / h, a 28d cumulative nitrogen and phosphorus release rate ≤40%, and a pH value of 6.5~7.
8.
6. A method for preparing reconstructed soil for soil stabilization and conservation on steep slopes as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S01: Weigh each component according to the proportion; S02: Mix γ-polyglutamic acid with a first part by weight of water to prepare a pre-solution; mix ammonium bicarbonate with a second part by weight of water to prepare a suspension; the sum of the first part by weight of water and the second part by weight of water is equal to the total amount of water weighed in S01; S03: Dry-mix waste concrete recycled fine aggregate, lithium magnesium silicate, polyvinylpyrrolidone-borax dual-network hydrogel dry powder, urea phosphate, and calcium nitrate tetrahydrate to obtain a dry-based mixture. S04: Add γ-polyglutamic acid pre-solution to the dry base mixture and mix wet, then add ammonium bicarbonate suspension and stir until foaming, controlling the material temperature not to exceed 25℃, to obtain foamed plastic mixture; S05: Mold the foamed plastic mixture, let it stand until it initially sets, cover it with a moisture-retaining material, and cure it in an environment of 10~30℃ and relative humidity ≥70% until it solidifies, thus obtaining the reconstructed soil.
7. The preparation method according to claim 6, characterized in that, In step S03, the dry mixing speed is 20~35 r / min and the time is 4~8 min; in step S04, the wet mixing speed is 25~40 r / min and the time is 3~5 min, and the foaming mixing speed is 15~25 r / min and the time is 1~3 min; in step S05, the molding process adopts static pressure or light vibration, the compaction pressure is ≤2MPa, and the curing time is 5~8 days.
8. The application of the soil stabilization and conservation type reconstructed soil according to any one of claims 1 to 5 in the soil covering reconstruction and ecological restoration of mine rock slopes, spoil heaps or quarry waste sites with a slope of ≥45°.
Citation Information
Patent Citations
Gamma-polyglutamic acid mixed fertilizer and desert treatment technology thereof
CN102515934B
Rock aging and repair agents for fresh rock wounds on steep slopes, their preparation methods and applications
CN113598013B
A lightweight material for vegetation restoration on steep slopes, its preparation method and application
CN114600731B
Low-alkali recycled eco-concrete with high vegetation performance and its construction method
CN116621548B
Ecological seed-carrying slurry for slope of mine dump, preparation method and application thereof
CN119349945B